PELAKSANAAN PENDIDIKAN DAN PELATIHAN BAGI PENYULUHAN PERTANIAN OLEH BALAI PELATIHAN PERTANIAN JAMBI BERDASARKAN PERATURAN MENTERI PERTANIAN NOMOR : 49/PERMENTAN/OT.140/9/2011 - Mhd Ansori (Universitas Batanghari Jambi, 2018)
In order to anticipate the challenges of the evolving strategic environment changes in this century of human resources required that ready-made, professional, innovative, creative, and insightful global. Education and training is one of the attempts to answer these challenges, as well as answer the new demands of society to obtain excellent service in the Ministry of education and training services as well as information to improve productivity, effectiveness, and efficiency of the main perpetrators of agribusiness ventures and agricultural trade in the countryside. This paper examines the principal issues, namely Whether the realization of the training participants were already in compliance with the results of the identification of Training Needs (IKD).Keywords: education and training, agricultural extension, Agricultural Training Hall